PENGUKURAN KUALITAS PELAYANAN PENDIDIKAN DENGAN METODE STUDENT SATISFACTION INVENTORY DI PROGRAM STUDI PENDIDIKAN MATEMATIKA - Istiqomah Istiqomah; Tri Astuti Arigiyati (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
The aim of this study was to measure the quality of service in Mathematics Education Study Program. This research is descriptive research, because this research will reflect the perceptions and expectations of students towards service quality in Mathematics Education Study Program. Sampling in this study conducted by random sampling technique.Instruments in this study was a questionnaire that serves to uncover and measure students' perceptions and expectations of service quality in Mathematics Education courses FKIP UST. The data analysis technique used is descriptive analysis techniques and calculation of the score gap. The results showed that the tendency of the rate of student satisfaction in the category are satisfied. While the tendency of the rate of satisfaction for each dimension is 9-dimensional in satisfied category and 2-dimensional in quite satisfied category. The tendency of the level of interest / expectations of students is very important category. Similarly, the tendency of the level of interest / expectations for each of these dimensions in the dimension 11 is very important category. The highest score gap lies in the dimensions of Campus Support Service which is equal to a score of 1.48 and the lowest gap lies in the dimensions of Academic Advising which is equal to 0.72. Variables are prioritized for repair are the variables that enter the first quadrant, in order to increase the level of student satisfaction.Keywords :academic services, Quality, Student Satisfaction Inventory method